BUNGA TERATAI SEBAGAI IDE PENCIPTAN KURSI TERAS - Bagus Dwymas Handono; Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2019)
When the body feels tired after work, it needs a place to rest and relax, the terrace chair as a relaxing facility needs a comfortable and functional design, in this case the lotus flower structure is the basic idea for creating a terrace chair that emphasizes function and aesthetic value.Lotus is the common name for the genus Nymphaea which is an aquatic plant. The lotus is characterized by flowers and leaves floating on the surface of the water. Several types of lotus have important influences in art including white lotus (kumuda), blue lotus (utpala), red lotus (Padma). According to Hindu and Buddhist beliefs, the lotus flower has a high spiritual level, namely as a symbol of purity. Meanwhile, the Islamic religion of the lotus is only an ornamental motif.The lotus flower as a form structure in the creation of a terrace chair is a creative and innovative design. The main function of providing relaxing comfort in the terrace room, a shape that resembles a lotus adds to the decorative value of the terrace space.